Essential Oil Composition and Physiology of Three Mentha Genotypes Under Shaded Field Conditions - Charlotte Hubert-Schöler; Saskia Tsiaparas; Katharina Luhmer; Marcel Dieter Moll; Maike Passon; Matthias Wüst; Andreas Schieber; Ralf Pude (Plants, 2024)
Mentha spp. are commonly used for the production of tea and for the extraction of essential oils (EOs). The key factor of mint quality is the content and composition of the EO. Health-promoting compounds such as menthol are desirable, whereas the presence of potentially health-damaging compounds such as menthofuran should be avoided. This study examines the effect of shading on the EO content and composition of three Mentha genotypes (Mentha × piperita ‘Multimentha’, Mentha × piperita ‘Fränkische Blaue’ and Mentha rotundifolia ‘Apfelminze’). The Mentha genotypes were cultivated in field trials for two years (2022–2023). Each genotype was shaded with a shading net (50% photosynthetic active radiation (PAR) reduction), and a control without shading was prepared. EO content was determined by steam distillation and EO composition was characterized by GC-MS analysis. Furthermore, biomass, vegetation indices (VIs) and the electron transport rate (ETR) were analyzed. While shading led to higher plant heights, higher EO content and a slightly reduced amount of undesired EO compounds, the unshaded control yielded a higher biomass accumulation. Significant genotypic differences were determined. In conclusion, the benefits of shading depend on the intended use and genotype selection.